Pathogenicity and virulence of Mycobacterium tuberculosis - Kathryn C. Rahlwes; Beatriz R.S. Dias; Priscila C. Campos; Samuel Alvarez-Arguedas; Michael U. Shiloh (Virulence)
Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis, an infectious disease with one of the highest morbidity and mortality rates worldwide. Leveraging its highly evolved repertoire of non-protein and protein virulence factors, Mtb invades through the airway, subverts host immunity, establishes its survival niche, and ultimately escapes in the setting of active disease to initiate another round of infection in a naive host. In this review, we will provide a concise synopsis of the infectious life cycle of Mtb and its clinical and epidemiologic significance. We will also take stock of its virulence factors and pathogenic mechanisms that modulate host immunity and facilitate its spread. Developing a greater understanding of the interface between Mtb virulence factors and host defences will enable progress toward improved vaccines and therapeutics to prevent and treat tuberculosis.